1988
DOI: 10.1007/bf02907179
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chromosome 5B on synapsis and chiasma formation in wheat, triticum aestivum cv. Chinese Spring

Abstract: The present paper summarizes and discusses the results obtained from a series of ultrastructural investigations of the effect of chromosome 5B on chromosome pairing and synaptonemal complex formation in wheat, T. aestivum cv. Chinese Spring. The material comprises hexaploid wheat nullisomic for chromosome 5B, monosomic for 5B, euploid wheat, wheat where chromosomes 5B have been replaced by one, two or three copies of an isochromosome for the long arm of chromosome 5B; trihaploid wheat with and without 5B and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 74 publications
3
54
0
Order By: Relevance
“…Chromosome pairing at prophase I of meiosis has, to date, been examined by synaptonemal complex analysis in two other allohexaploids, namely Triticurn aestivurn (Hobolth, 1981;Jenkins, 1983;Hoim, 1986;Holm & Wang, 1988) and Avena sativa (Jones et a!., 1989). …”
Section: Introductionmentioning
confidence: 99%
“…Chromosome pairing at prophase I of meiosis has, to date, been examined by synaptonemal complex analysis in two other allohexaploids, namely Triticurn aestivurn (Hobolth, 1981;Jenkins, 1983;Hoim, 1986;Holm & Wang, 1988) and Avena sativa (Jones et a!., 1989). …”
Section: Introductionmentioning
confidence: 99%
“…A summary and discussion of the results obtained from this analysis as well as a general discussion of the effect of chromosome 5B are given in a separate paper (4).…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery some 50 years ago, cytological investigations of wheat mutants that lack the Ph1 locus have shown that there are several defects that occur during pre-meiotic interphase and early meiosis that contribute to the homoeologous chromosome pairing observed at metaphase I (Riley and Chapman 1958;Sears 1977;Holm and Wang 1988). Initial studies showed that synapsis is arrested in ph1 mutants, to a level of~35-40% of wild-type wheat (Holm and Wang 1988).…”
Section: The Classical Geneticsmentioning
confidence: 99%
“…In addition, multiple axial element associations that normally occur during zygotene are not resolved into homologous chromosome pairs in ph1 mutants like they are in wild-type wheat (Holm and Wang 1988). Based on these observations, Holm and Wang (1988) proposed that the alignment of homologous chromosomes is affected in ph1 mutants, preventing the correction of multiple axial element associations.…”
Section: The Classical Geneticsmentioning
confidence: 99%
See 1 more Smart Citation